Biomimetic polydopamine catalyst with redox activity for oxygen-promoted H2 production via aqueous formaldehyde reforming. Issue 18 (23rd August 2021) - Du, Leilei; Wang, Gang; Yan, Xiaoqing; Kobayashi, Hisayoshi; Li, Sha; Li, Renhong; Chen, Wenxing
Abstract : We report for the first time that biomimetic polydopamine (PDA) nanoparticles are catalytically active for formaldehyde (HCHO) reforming into hydrogen (H2 ), where O2 acts as a co-catalyst. Abstract : We report for the first time that biomimetic polydopamine (PDA) nanoparticles are catalytically active for formaldehyde (HCHO) reforming into hydrogen (H2 ), where O2 acts as a co-catalyst. The catechol in PDA can activate O2 molecules to form ˙OOH and semiquinone radicals, which facilitate water dissociation and HCHO decomposition to realize efficient H2 production. This work offers new insights into the design of organic catalysts for aqueous-phase hydrogen evolution reactions.